Ferroptosis and immunity: a bibliometric analysis of research hotspots and frontiers (2012-2025) - Huang, Qi; Feng, Shuhang; He, Changhao; Xu, Rong; Cai, Yixuan; Guan, Linyu; Guan, Jiaqi; Wang, Lei (Frontiers in Immunology, 2026)
BackgroundFerroptosis is a form of programmed cell death triggered by iron-dependent lipid peroxidation. Accumulating evidence has revealed potential associations between cellular Ferroptosis and infection, inflammation, and immunity. Given the substantial literature in this field, the present study aims to comprehensively overview the research hotspots and knowledge structure underlying the interplay between Ferroptosis and immunity via bibliometric analysis.MethodsRelevant literature focusing on Ferroptosis and immunity—published between January 1, 2012, and August 31, 2025—was retrieved from the Web of Science, PubMed, and Scopus databases. Bibliometric analyses, encompassing evaluations of national contributions, institutional collaborative networks, journal outputs, and keyword co-occurrence, were conducted using CiteSpace, VOSviewer, and Origin software. These analyses aimed to delineate research trends and project future research trajectories.ResultsA total of 3,436 publications relevant to Ferroptosis and immunity were included in this study. The analysis revealed a continuous and steady growth in the number of articles published in this field over the past 12 years. At the national level, China leads in both publication output (H-index = 99) and institutional contributions, with Central South University and Sun Yat-sen University each accounting for 154 papers. In contrast, the United States (average citations per paper: 114.11) and Germany (average citations per paper: 142.92) demonstrate outstanding performance in research impact. Frontiers in Immunology stands out as the most prolific journal, with 162 published articles in this field. Keyword co-occurrence analysis indicated that the application of Ferroptosis in cancer immunotherapy currently constitutes the most prominent research focus.ConclusionThis study represents the first systematic bibliometric analysis of literature on Ferroptosis and immunity, leveraging data from the Web of Science, PubMed, and Scopus databases. These findings underscore that oncology and immunology are the dominant disciplines in this field, with Ferroptosis-targeted cancer immunotherapies and the modulation of the tumor immune microenvironment (TME) emerging as key frontiers. Strengthening international collaboration and focusing on high-impact research will facilitate the clinical translation of therapeutic strategies for immunity-related diseases.